1999
DOI: 10.1038/sj.bjp.0702445
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of stretching behaviour induced by the selective 5‐HT6 receptor antagonist, Ro 04–6790, in rats

Abstract: 1 The present study examined the eects of the selective 5-HT 6 receptor antagonist 4-amino-N-(2, 6 bis-methylamino-pyrimidin-4-yl)-benzene sulphonamide (Ro 04-6790) on locomotor activity and unconditioned behaviour in male Sprague Dawley rats (230 ± 300 g). , i.p.) was signi®cantly greater than that observed in saline-treated rats. The yawning behaviour, however, was not dose-dependent nor was the number of yawns in any of the drug treated groups signi®cantly greater than in those treated with saline. 6 These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 24 publications
4
59
0
2
Order By: Relevance
“…The present data suggest that it may involve an increase in cholinergic transmission (Riemer et al, 2003;Shirazi-Southall et al, 2002). Previous behavioral studies indicated such an enhanced cholinergic neurotransmission after administration with a 5-HT 6 antagonist (Bentley et al, 1999). The present finding that Ro4368554 reversed a scopolamine-induced deficit in novel object recognition corroborates other studies showing scopolamine reversal in cognition tasks (Foley et al, 2004;Meneses, 2001;Woolley et al, 2003).…”
Section: Neurochemical Mechanisms Involved In the Effects Of 5-ht 6 Asupporting
confidence: 90%
“…The present data suggest that it may involve an increase in cholinergic transmission (Riemer et al, 2003;Shirazi-Southall et al, 2002). Previous behavioral studies indicated such an enhanced cholinergic neurotransmission after administration with a 5-HT 6 antagonist (Bentley et al, 1999). The present finding that Ro4368554 reversed a scopolamine-induced deficit in novel object recognition corroborates other studies showing scopolamine reversal in cognition tasks (Foley et al, 2004;Meneses, 2001;Woolley et al, 2003).…”
Section: Neurochemical Mechanisms Involved In the Effects Of 5-ht 6 Asupporting
confidence: 90%
“…In the absence of binding data, data from other pharmacological and biochemical studies revealing activity at the respective receptors were used to select relevant doses (see e.g. Nomikos et al 1992;Andersson et al 1994Andersson et al , 1995Nomikos et al 1994;Bentley et al 1999;Grottick et al 2000;Marcus et al 2000). For example, based on a number of previously published preclinical data Andersson et al 1995;, it is estimated that full occupancy and blockade of D2 receptors in the brain is achieved by the dose of raclopride used.…”
Section: Discussionmentioning
confidence: 99%
“…ketanserin, ritanserin, and mesulergine, which exhibit varying degrees of 5-HT 2A vs. 5-HT 2C receptor selectivity (Hirano et al 1995;Consolo et al 1996;Zhelyazkova-Savova et al 1999). Interestingly, both clozapine and olanzapine, in contrast to other antipsychotic drugs tested, appear to show high affinity for the 5-HT 6 receptors (Roth et al 1994;Bymaster et al 1999), and 5-HT 6 receptor antagonists purportedly increase cholinergic function in the brain (Bentley et al 1999). Accordingly, selective action at the 5-HT 6 receptors could account for the pronounced effects of clozapine and olanzapine on hippocampal ACh outflow, as compared with the other antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that 5-HT 6 R antisense oligonucleotides (Bourson et al, 1995;Sleight et al, 1996) or 5-HT 6 R antagonists (Unsworth and Molinoff, 1994;Sleight et al, 1998;Bentley et al, 1999;Routledge et al, 1999) produced yawning-stretching behaviors that could be blocked by the muscarinic cholinergic antagonist atropine or potentiated by the cholinesterase inhibitor physostigmine. Other studies have implicated Rs in the modulation of cognitive processes (Russell and Dias, 2002).…”
Section: -Ht 6 R-influenced Behaviorsmentioning
confidence: 99%
“…Thus, the expression pattern and pharmacological properties of Rs indicate that they may contribute to serotonergic modulation of clinically relevant neuropsychological processes and psychopharmacological responses. Administration of 5-HT 6 R antagonists and antisense oligonucleotides have been reported to produce several behavioral effects in rodents, including feeding suppression (Svartengren et al, 2004), yawning and stretching (Bourson et al, 1995;Sleight et al, 1996;Sleight et al, 1998;Bentley et al, 1999), decreased anxiety-related behaviors (Hamon et al, 1999), and improved performance in learning and memory tasks (Meneses, 2001;Rogers and Hagan, 2001;Woolley et al, 2001;Russell and Dias, 2002;Lindner et al, 2003;Riemer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%